Pola Asuh Orang Tua dan Lingkungan Sosial dalam Menumbuhkan Akidah pada Anak Usia Dini - Siti Maryam; Devy Habibi Muhammad; Ari Susandi (Edumaspul: Jurnal Pendidikan, 2021)
As the main burden of family education, growing the creed from an early age must be closely monitored by parents. Aqidah education given to children by the family can be used as a step to keep them from deviant behavior and free them from moral depravity. In order for high moral children to realize this, as parents, one must instill a high creed. Therefore, along with the higher trust in children, the pattern of parental guidance is very important in doing it early on. The formulation of the problem is how the pattern of parental guidance and the social environment that develops beliefs or beliefs to early childhood and the factors that affect it. The purpose of this study is to find out the parenting and social environment in cultivating early childhood faith and the factors that affect the process of early childhood faith growth. This research is a library research technique (library research) data collection technique in this study is to read and record the information contained in the data.The results of this study suggest that parental parenting and social environments can increase trust in early childhood. In increasing early childhood confidence there are various methods that can be lived by parents is to educate habituation, example, advice and praise or reprimand. While in growing the faith in children precisely in the social environment that can be done by getting used to good things in children and paying attention to the child's social association. If the parenting of parents and the social environment in growing the creed in children is good, it will affect the character of the child.